2012
DOI: 10.1103/physreva.85.039907
|View full text |Cite
|
Sign up to set email alerts
|

Publisher’s Note: Interplay between permanent dipole moments and polarizability in positron-molecule binding [Phys. Rev. A85, 022709 (2012)]

Abstract: Publisher's Note: Interplay between permanent dipole moments and polarizability in positron-molecule binding [Phys. Rev. A 85, 022709 (2012)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…In spite of the fact that most of the molecules had unphysical values of r 0 , it was found that taking the value of µ and r 0 for the molecule in each chemical family with the median dipole moment and varying the polarizability to match the other molecules in the family, gave reliable predictions of the binding energies for those molecules (with the exception of the methyl halides). The perturbative treatment was also in line with the observation made by experimentalists, that the dependence of the binding energy on the polarizability of the molecule is apparently almost linear [7]. Of course, a general increase in the binding energy with the polarizability could be expected, but there was no explanation for the linear dependence.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In spite of the fact that most of the molecules had unphysical values of r 0 , it was found that taking the value of µ and r 0 for the molecule in each chemical family with the median dipole moment and varying the polarizability to match the other molecules in the family, gave reliable predictions of the binding energies for those molecules (with the exception of the methyl halides). The perturbative treatment was also in line with the observation made by experimentalists, that the dependence of the binding energy on the polarizability of the molecule is apparently almost linear [7]. Of course, a general increase in the binding energy with the polarizability could be expected, but there was no explanation for the linear dependence.…”
Section: Discussionsupporting
confidence: 85%
“…the dependence of ǫ b on α for molecules within the same chemical family (i.e., aldehydes, ketones, formates, acetates, nitriles) to be almost linear [7]. From (26) we can see that, for fixed µ and r 0 , ǫ (1) b scales linearly with α.…”
Section: Core Radii For Perturbative Inclusion Of Polarizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, by observing the resonances, the positron binding energy ε b = |ǫ 0 | can be found. In this way binding energies for over sixty polyatomic species have been determined [22][23][24][25] by measuring positron annihilation using a high-resolution, tunable, trap-based positron beam [26]. In our previous paper [13] we suggested that one can search for a similar effect in atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, by observing the resonances, the positron binding energy can be found. In this way, binding energies for over 60 polyatomic species have been determined [26][27][28][29] by measuring positron annihilation using a high-resolution, tunable, trap-based positron beam [30].…”
Section: Introductionmentioning
confidence: 99%